Why Study Religion from a Latin American Sociological Perspective? An Introduction to Religions Issue, “Religion in Latin America, and among Latinos Abroad” - Gustavo Morello (Religions, 2019)
This article introduces the Religions issue on Latin American religiosity exploring sociological perspectives on the Latin American religious situation, from a Latin American perspective. The Secularization Theory proposes “the more modernity, the less religion”, but in Latin America we see both, modernity and religiosity. The Religious Economy model, on the other hand, affirms “the more pluralization, the more religion”, but in Latin America there is not so much pluralization, and it is not easy to switch from one religion to other. Finally, the article presents a Latin American model, the “popular religiosity” one. The problem with it, is that it is mostly ‘Catholic,’ and so does not account for the growing religious diversity in the region. It also emphasizes the “popular” aspect, excluding middle socioeconomic status individuals and elites, assuming they practice “real” religion. This introduction presents a critical approach as a way to recover, describe, and understand Latin American religious practices. This methodology might be a path to creating sociological categories to understand religion beyond the north Atlantic world.